Ischemic preconditioning/ischemic postconditioning alleviates anoxia/reoxygenation injury via the Notch1/Hes1/VDAC1 axis. Issue 11 (17th August 2022) - Wang, Lijun; Lai, Songqing; Zou, Huaxi; Zhou, Xueliang; Wan, Qing; Luo, Yong; Wu, Qicai; Wan, Li; Liu, Jichun; Huang, Huang
Abstract: Ischemic preconditioning (IPC), and ischemic postconditioning (IPost) have a significant protective effect on myocardial ischemia/reperfusion (MI/R) injury by alleviating oxidative stress and mitochondrial disturbances, although the underlying molecular mechanisms are unclear. The study was to demonstrate that cardioprotection against anoxia/reoxygenation (A/R) injury is transduced via the Notch1/Hes1/VDAC1 signaling pathway. Using mass spectrometry and tandem affinity purification (TAP), to screen for differentially expressed proteins associated with Hes1, followed by standard bioinformatics analysis. The co‐immunoprecipitation (Co‐IP) assay confirmed an interaction between Hes1 and VDAC1 proteins. H9c2 cells were transfected with Hes1 adenoviral N‐terminal TAP vector (AD‐NTAP/Hes1) and Hes1‐short hairpin RNA adenoviral vector (AD‐Hes1‐shRNA) to establish A/R injury, IPC, and IPost models, respectively. The expression of Hes1 and VDAC1 proteins were measured by western blot analysis, while the levels of reactive oxygen species (ROS), mitochondrial membrane potential (ΔΨm), and apoptosis were evaluated by flow cytometry. AD‐NTAP/Hes1 can activate the exogenous protein expression of Hes1, thus decreasing creatine phosphokinase (CPK) and lactate dehydrogenase (LDH) activity and promoting cell viability. The study found that VDAC1 was a potential target protein for Hes1 and the overexpression of Hes1 protein expression downregulated protein expression levels of VDAC1, reduced ROS production, stabilized ΔΨm, and inhibited apoptosis in H9c2 cells. Additionally, downregulation of Hes1 protein expression also upregulated VDAC1 protein expression, increased ROS production, imbalanced ΔΨm, promoted cell apoptosis, and attenuated the cardioprotection afforded by IPC and IPost. The Notch1/Hes1 signaling pathway activated by IPC/IPost can directly downregulate the protein expression of VDAC1 and consequently relieve A/R injury.